The Ritual of the Habitual: Introductory Notes on a Peruvian National Rock Music - López Ramírez Gastón, José Ignacio (2020)
The involvement of rock music in the development of music communities in Peru is an unexplored theme in the academic world. In the construction of national and regional models of a distinctive musicality, popular urban music of foreign origin has not been considered; nor has it been considered as an element in the formation of an identity governed by the discursive parameters of the nation-state. In this work, we explore the confrontations and dichotomies that are maintained as foreign in the subject of rock and in the communities of national and global rock music.